Biomechanics of Yoga: Understanding the Biomechanics of Yoga for Self-Improvement and Harmony (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Yoga is a saàskta term with several meanings, but most often refers to affixing or joining(an individual consciousness with the supreme consciousness). Sage Patajali developed this school ofthought, one of the six traditional schools of Indian philosophy. Yoga, according to Sage Patajali, is not astate of oneness but rather a disjunction, a dividing of the spiritual principle from the material principle.It's the world's first comprehensive approach to self-improvement, focusing on the whole person ratherthan just one aspect. The ancient sages had a deep comprehension of man's inherent nature and the needof living in harmony with one's self and one's surroundings. Yoga is both a science and an art because ofthis.In this paper the discuss the Biomechanics of yoga.